1971
DOI: 10.1086/129155
|View full text |Cite
|
Sign up to set email alerts
|

Photometry of Three Peculiar A-Type Stars

Abstract: Four-color (uvby) photoelectric observations have yielded provisional periods for three peculiar A-type stars. For 108 Aquarii, the period is 3^73. For HD 184905, the period is either 1^84 or 2^17, and for 0 1 Microscopii the most probable periods are 0^941 and 1^062.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1975
1975
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…But those of b and y are nearly symmetric. Morrison & Wolff (1971) As this was similar to the changes in the shape of the light curves of 56 Ari reported by Adelman & Fried (1993) who interpret this type of behavior as due to free body precession of the magnetic CP star, additional photometric FCAPT observations of this star were made in the fall of 1995 using the same comparison and check stars. Almost all the 146 new observations observations were made during one month with many observations per night.…”
Section: Hr 2258 (= Hd 43819)supporting
confidence: 79%
“…But those of b and y are nearly symmetric. Morrison & Wolff (1971) As this was similar to the changes in the shape of the light curves of 56 Ari reported by Adelman & Fried (1993) who interpret this type of behavior as due to free body precession of the magnetic CP star, additional photometric FCAPT observations of this star were made in the fall of 1995 using the same comparison and check stars. Almost all the 146 new observations observations were made during one month with many observations per night.…”
Section: Hr 2258 (= Hd 43819)supporting
confidence: 79%
“…In spite of the few observations, it is to be noted the outstanding amplitude, of the order of 0.1 mag, the largest observed until now. The photometric variability of HD 223640 has been studied in the Strömgren system by Morrison & Wolff (1971) who found a period of 3.73 d. The light curves show quite the same behaviour in all filters with a fairly constant amplitude of about 0.06 mag peak to peak. Megessier & Garnier (1972) contributed a few photometric data again in the Strömgren system and checked the spectroscopic variability; these authors found the Ti and Sr lines strongly variable and the lines of Fe constant.…”
Section: Hd 187473 = Gc 27467 = V4064 Sgrmentioning
confidence: 99%
“…The first determination of the period has been performed by Morrison & Wolff (1971); from uvby observations these authors found HD 203006 to vary within 1.062 ± 0.001 d. Maitzen et al (1974) found a double wave in their UBV and uvby observations and stated the correct period to be 2.1219 d. From more recent photoelectric observations Deul & van Genderen (1983) Table 3. The solid line is a least-square fit of the observations by Eq.…”
Section: Hd 153882 = Hr 6326 = V451 Hermentioning
confidence: 99%